Distribution of Zakat Fitrah in Lebeng Barat Village from an Islamic perspective - Nurul Hidayati, Nurul; Wahyuni, Sri (Al-Hiwalah: Journal of Sharia Economic Law, 2024)
Zakat is one of the main pillars of Islam, which is an obligation for Muslims according to the command of the Shari'a. In the Qur'an, Allah SWT equates the importance of zakat with a very great worship, namely prayer, by mentioning it in eighty-two verses, emphasizing how great the value of zakat is. The purpose of this study is to determine how the provisions for the distribution of zakat are according to Islamic teachings and how Islamic law reviews the distribution of zakat fitran in Lebeng Barat Village. The method used is descriptive qualitative research with library research methods. The results show that the people of Lebeng Barat Village, Pamekasan are already aware of their obligation to pay zakat, the people of Lebeng Barat Village, Sumenep, from the 8 groups mentioned in the Qur'an only distribute to 4 groups. Regarding Muzakki outside the domicile, they pay zakat fitrah twice, which should be distributed to the poor in the area of ​​the person paying zakat. Even though it is permissible to send zakat fitrah to other areas, the reason must be based on factors of need or benefit, not because of kinship or place of birth